The Influence of Celebrity Endorsement and Free Shipping on The Originote Product Purchase Decision Via TikTok Shop (Case Study on The Originote Consumers in Bogor City) - Kuraesin, Ecin; Agustini, Salsa Bilah; Marlina, Asti (prodima@fe.uika-bogor.ac.id, 2024)
This study aims to determine the effect of celebrity endorsement and free shipping on purchasing decisions for the originote product through tiktok shop in Bogor City. This type of research used is quantitative. The population in this study were consumers who used the originote in Bogor City. The analysis used uses quantitative techniques with a sample size of 100 respondents. The instrument used in this study was a questionnaire. The results of the research instrument test using multiple regression analysis tests, t tests and f tests, which show that celebrity endorsement and free shipping have a significant effect on purchasing decisions with multiple regression analysis results of Y = 6.236 + 0.373X1 + 0.320X2. The results of the celebrity endorsement t test were obtained at t count 4.266> t table 1.984 which means Ho1 is rejected and Ha1 is accepted. While the free shipping t test is t count 3.563> t table 1.984 which means Ho2 is rejected and Ha2 is accepted, where there is an influence between free shipping on purchasing decisions. And the results of the f test obtained by f count 23.912> f table 3.09 mean that Ho3 is rejected and Ha3 is accepted, where there is a simultaneous influence on purchasing decisions for the originote product through tiktok shop in the Bogor City area.